p - Fitri Hayati; Adisty Aulia Zahra; Widya Anggraini; Yauma Afriyanti; Amanda Mutiara Hasibuan (Universitas Veteran Bangun Nusantara, 2025)
This study employs a qualitative method with a literature review approach to examine the economic thought of al-Ghazali, a prominent scholar in the Islamic intellectual tradition renowned not only for his contributions to Sufism and philosophy but also for his insights into economic and social ethics. The research aims to explore situs big77 al-Ghazali’s contributions to Islamic economics, particularly in the framework of justice, ethical trade, and equitable wealth distribution. The study begins by tracing a brief biography of al-Ghazali, his intellectual journey, and his leadership in the classical Islamic scholarly world. The discussion then focuses on his core economic thoughts as reflected in his works such as *Ihya’ Ulum al-Din* and *al-Mustasfa*, which emphasize the balance between spiritual and material needs in economic activity. The research also explores the impact of al-Ghazali’s economic thought during the caliphate era and its relevance in modern economic contexts, especially in addressing challenges related to wealth distribution and business ethics. The findings indicate that al-Ghazali’s ideas remain relevant and can serve as a reference for developing an Islamic economic system grounded in justice and oriented toward public welfare.